2020
DOI: 10.3389/fmicb.2020.01228
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens Small Lipoprotein Atu8019 Is Involved in Selective Outer Membrane Vesicle (OMV) Docking to Bacterial Cells

Abstract: Outer membrane vesicles (OMVs), released from Gram-negative bacteria, have been attributed to intra-and interspecies communication and pathogenicity in diverse bacteria. OMVs carry various components including genetic material, toxins, signaling molecules, or proteins. Although the molecular mechanism(s) of cargo delivery is not fully understood, recent studies showed that transfer of the OMV content to surrounding cells is mediated by selective interactions. Here, we show that the phytopathogen Agrobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 94 publications
0
22
0
Order By: Relevance
“…Bacterial EVs contain immunogenic molecules such as EF-Tu and LPS, and can contain digestive enzymes and effectors that undermine host defences (Bahar et al , 2016, Feitosa-Junior et al , 2019, Knoke et al , 2020, Rybak & Robatzek, 2019). To determine the effect of EVs from Pto DC3000 on plant cells, we first examined the ability of the Pto DC3000 EVs to modulate the outcome of bacterial infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial EVs contain immunogenic molecules such as EF-Tu and LPS, and can contain digestive enzymes and effectors that undermine host defences (Bahar et al , 2016, Feitosa-Junior et al , 2019, Knoke et al , 2020, Rybak & Robatzek, 2019). To determine the effect of EVs from Pto DC3000 on plant cells, we first examined the ability of the Pto DC3000 EVs to modulate the outcome of bacterial infection.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed a number of molecular cargoes present in EVs from phytopathogenic bacteria of the Agrobacterium tumefaciens, P. syringae, Xanthomonas campestris and Xylella fastidiosa species. These EV-associated proteins include degradative enzymes, Type-II-secreted virulence-associated proteins, components of the Type-III secretion system and its secreted proteins (Feitosa-Junior et al , 2019, Chowdhury & Jagannadham, 2013, Knoke et al , 2020, Nascimento et al , 2016, Sidhu et al , 2008, Sole et al , 2015). While respective genetic deletions of EV-associated degradative enzymes reduced bacterial virulence, the role of EVs in their delivery remained unanswered (Nascimento et al , 2016, Sidhu et al , 2008, Sole et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…pathway (Kaplan et al, 2018), after which it remains at the periplasmic site or is transported to the cell surface (Knoke et al, 2020). Stress can alter the structure of peptidoglycan or Lpp, leading to membrane blebbing due to the loss of membrane integrity; the balance between peptidoglycan turnover and elements that preserve membrane integrity through lipoprotein crosslinking determines the degree of membrane vesiculation (Martins et al, 2019;Ultee et al, 2019).…”
Section: Role Of Inner Membrane For Omv Productionmentioning
confidence: 99%
“…After their export through the cytoplasmic membrane, which occurs predominantly but not exclusively via the general secretory (Sec) pathway, the proteins are modified with lipids at the cytoplasmic membrane in a multistep process ( Zückert, 2014 ). Depending on N -acylation and specific sorting signals, Lpp (the best known crosslinked lipoprotein) either remains in the inner membrane or is translocated to the inner leaflet of the outer membrane via the Lpp outer membrane localization pathway ( Kaplan et al, 2018 ), after which it remains at the periplasmic site or is transported to the cell surface ( Knoke et al, 2020 ). Stress can alter the structure of peptidoglycan or Lpp, leading to membrane blebbing due to the loss of membrane integrity; the balance between peptidoglycan turnover and elements that preserve membrane integrity through lipoprotein crosslinking determines the degree of membrane vesiculation ( Martins et al, 2019 ; Ultee et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation